Exploring the Influence of Green Marketing on Green Customer Loyalty for Eco-friendly resorts in Phuket Island - Jain, Mahima; Nuangjamnong, Chompu (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2024)
Purpose – This study aims to analyze the relationship of green marketing, customer trust, green image, customer satisfaction on green customer loyalty for eco-friendly resorts in Phuket Island. Design/Methodology/Approach – The research aims to use primary and secondary data gathering methods to perform an analysis to explore the influence of green marketing on green customer loyalty for Phuket Island’s eco-friendly resorts. The information was gathered from 390 respondents who had visited Phuket Island’s eco-friendly resorts. In order to develop the conceptual framework, this study referred to four existing theoretical frameworks. Findings – This study is intended to explore the influence of green marketing on green customer loyalty. Followed by the findings of this research represented green marketing has a significant influence on customer satisfaction whereas customer trust has no significant influence on customer satisfaction. Green marketing, customer satisfaction and customer trust have a significant influence on green customer loyalty. However, green image has no significant influence on green customer loyalty. Research Limitations/Implications – The limitations of the research showed several elements to explore the influence of green marketing on green customer loyalty for eco-friendly resorts in Phuket Island. The study's focus on Phuket visitors may not apply to other eco-tourism locations, and eco-friendly resorts were preferred over other accommodations. Quantitative methods may overlook factors influencing tourist decisions, while qualitative methods like focus groups or interviews provide more in-depth insights. The sample size of 390 respondents may not accurately represent green tourists. Originality/value – This study on the influence of green marketing on green customer loyalty for eco-friendly resorts in Phuket Island. Keywords – Green Marketing, Customer Trust, Green Image, Customer Satisfaction, Green Customer Loyalty. JEL classification code – Z30, Z31, Z32, Z33